Tunable negative permittivity based on phenolic resin and multi-walled carbon nanotubes. Issue 22 (6th February 2015) - Qian, Lei; Lu, Lu; Fan, Runhua
Abstract : Tunable negative permittivity was produced from phenolic resin with three-dimensional conductive networks of multi-walled carbon nanotubes. Abstract : We first reported tunable negative permittivity from phenolic resin (PhR) and multi-walled carbon nanotubes (MWNTs). Different amount of MWNTs were incorporated into the PhR matrix, and the morphologies of the PhR–MWNT materials were characterized using field emission scanning electron microscopy. Dielectric, conductive and impedance performance were investigated in detail. When the MWNT content was above 14.00 vol%, negative permittivity was obtained which was obviously different from that with a low MWNT content. Moreover, the negative permittivity was tuned by adjusting the MWNT content in the matrix. The equivalent circuit analysis indicated that the PhR–MWNT material with negative permittivity corresponded to an inductive element. The appearance of negative permittivity was attributed to the presence of three-dimensional conductive networks of MWNT in the PhR matrix.